A central role for the ERK-signaling pathway in controlling Schwann cell plasticity and peripheral nerve regeneration in vivo - Napoli, Ilaria; Noon, Luke A; Ribeiro, Sara; Kerai, Ajay P; Parrinello, Simona; Rosenberg, Laura H; Collins, Melissa J; Harrisingh, Marie C; White, Ian J; Woodhoo, Ashwin; Lloyd, Alison C (Neuron (Cambridge, Mass.), 2012)
Following damage to peripheral nerves, a remarkable process of clearance and regeneration takes place. Axons downstream of the injury degenerate, while the nerve is remodeled to direct axonal regrowth. Schwann cells are important for this regenerative process. "Sensing" damaged axons, they dedifferentiate to a progenitor-like state, in which they aid nerve regeneration. Here, we demonstrate that activation of an inducible Raf-kinase transgene in myelinated Schwann cells is sufficient to control this plasticity by inducing severe demyelination in the absence of axonal damage, with the period of demyelination/ataxia determined by the duration of Raf activation. Remarkably, activation of Raf-kinase also induces much of the inflammatory response important for nerve repair, including breakdown of the blood-nerve barrier and the influx of inflammatory cells. This reversible in vivo model identifies a central role for ERK signaling in Schwann cells in orchestrating nerve repair and is a powerful system for studying peripheral neuropathies and cancer.